2007
DOI: 10.1021/jo0625406
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies of Ce(IV)-Mediated Oxidation of β-Dicarbonyls:  Solvent-Dependent Behavior of Radical Cation Intermediates

Abstract: The Ce(IV)-initiated oxidation of synthetically relevant beta-diketones and beta-keto silyl enol ethers was explored in three solvents: acetonitrile, methylene chloride, and methanol. The studies presented herein show that the rate of reaction between Ce(IV) and the substrates is dependent upon the polarity of the solvent. Thermochemical studies and analysis are interpreted to be consistent with transition state stabilization by solvent being primarily responsible for the rate of substrate oxidation. Kinetic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 50 publications
(44 reference statements)
4
18
0
Order By: Relevance
“…Previous research from our group has shown that the oxidation of the enol tautomer of a diketone initially forms a radical cation, which is deprotonated readily by MeOH to form the radical under the reaction conditions [1516]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research from our group has shown that the oxidation of the enol tautomer of a diketone initially forms a radical cation, which is deprotonated readily by MeOH to form the radical under the reaction conditions [1516]. …”
Section: Resultsmentioning
confidence: 99%
“…In a previous study by our research group, the rates of oxidation of several β-diketones and their related silyl enol ethers by CAN and the more lipophilic ceric tetra- n -butylammonium nitrate (CTAN) were measured in MeOH, MeCN and CH 2 Cl 2 by using stopped-flow spectrophotometry [16]. In these experiments, initial oxidation of substrates generated radical cation intermediates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this mechanism, while Ce +4 is reduced to Ce +3 a radical cation B is formed. 48 Then, addition of the radical to the terminal double bond of the diene forms an allylic radical intermediate C. Radical C is oxidized to the carbocation D by CAN, followed by cyclization of D to give 5-(2-phenylvinyl)-4,5-dihydrofuran E. Intermediates F and H which is the another enol form of F were obtained from the radical addition of 1-phenyl-1,3-butanedione 1f to diene 2b. Intramolecular cyclization of these intermediates gave dihydrofurans G and I, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Coupling of 2 and 6 produces intermediate 7. A second equivalent of Ce IV oxidizes 7 to 8, which undergoes b elimination of the silyl cation through reaction with a nucleophile present in solution according to a known nucleophilic displacement mechanism, 12 providing iminium intermediate 9. Finally, 3 is released by the addition of one equivalent of H 2 O to 9, generating product 4 and a proton which must be absorbed by a base to prevent protonation of 3.…”
mentioning
confidence: 99%